1998
DOI: 10.1034/j.1399-3054.1998.1030306.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pyruvate,orthophosphate dikinase (PPDK) activity alters carbon metabolism in C3 transgenic potatoes with a C4 maize PPDK gene

Abstract: Changes in carbon metabolism and δ13C value of transgenic potato plants with a maize pyruvate,orthophosphate dikinase (PPDK; EC 2.7.9.1) gene are reported. PPDK catalyzes the formation of phosphoenolpyruvate (PEP), the initial acceptor of CO2 in the C4 photosynthetic pathway. PPDK activities in the leases of transgenic potatoes were up to 5.4‐fold higher than those of control potato plants (wild‐type and treated control plants). In the transgenic potato plants, PPDK activity in leaves was negatively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…In earlier attempts to increase PEPCase (Hudspeth et al 1992;Kogami et al 1994;Gehlen et al 1996), NADP-malate dehydrogenase (Gallardo et al 1995) or PPDK (Ishimaru et al 1997(Ishimaru et al , 1998 activities in transgenic plants, the respective authors have used chimeric genes containing cDNAs for C 4 enzymes under promoters such as rice Cab or CaMV 35S. The activities of their heterogeneous enzymes were less than 6-fold higher than those of wild-type plants.…”
Section: Discussionmentioning
confidence: 95%
“…In earlier attempts to increase PEPCase (Hudspeth et al 1992;Kogami et al 1994;Gehlen et al 1996), NADP-malate dehydrogenase (Gallardo et al 1995) or PPDK (Ishimaru et al 1997(Ishimaru et al , 1998 activities in transgenic plants, the respective authors have used chimeric genes containing cDNAs for C 4 enzymes under promoters such as rice Cab or CaMV 35S. The activities of their heterogeneous enzymes were less than 6-fold higher than those of wild-type plants.…”
Section: Discussionmentioning
confidence: 95%
“…Pyruvate orthophosphate dikinase, a key enzyme of the C 4 pathway, catalyzes the formation of phosphoenolpyruvate (PEP), the initial acceptor of CO 2 in the C 4 pathway [26]. The formation of PEP by PPDK is considered to be the rate-limiting step for the lowest reaction rate in the C 4 pathway [27,28]. Our results lead us to believe that U. linza may perform C 4 photosynthetic pathway and contribute to the large-scale bloom of U. linza.…”
mentioning
confidence: 99%
“…Several approaches have been carried out to overexpress PPDK in C 3 plants, including Arabidopsis (Ishimaru et al 1997;Voll et al 2003), potato (Ishimaru et al 1998), tobacco (Sheriff et al 1998) and rice (Nomura et al 2000;Fukayama et al 2001). In tobacco, it has been previously reported that the overexpression of the chloroplast-targeted M. crystallinum PPDK gene under the transcriptional control of the 35S promoter increased the number of seeds per seed capsule and the weight of each seed capsule by approximately 40% and 20%, respectively, with about a 1.5-fold increase in PPDK activity in leaves (Sheriff et al 1998).…”
Section: Discussionmentioning
confidence: 99%